Peran Gender sebagai Variabel Moderating Pembelajaran Perbankan Syariah, Literasi Keuangan Syariah, Religiusitas, Inklusi Keuangan Syariah Terhadap Minat Menabung Bank Syariah - Purnamawati Setyo Puji; Luqman Hakim (Jurnal Pendidikan Akuntansi (JPAK), 2021)
The development of Indonesian Islamic financial institutions, especially in the field of Islamic banking, has seen an increase every year, where Indonesia is in 5th place in the world, with banking products that have increased, namely savings products, but students at Surabaya State Universities have minimal interest in saving at Islamic Bank. This research aims to analyze the impact of Islamic banking learning, Islamic financial literacy, religiosity and Islamic financial inclusion on the interest in saving in Islamic banking with gender as a moderating variable for students of State Universities in Surabaya. This type of research is quantitative using a sample of 100 respondents from four state universities in Surabaya with data collection methods in the form of questionnaires and tests. The data analysis used was Structural Equation Modeling (SEM). The results of this research conclude that learning Islamic banking, religiosity and financial inclusion have a significant effect and financial literacy does not have a significant impact on interest in saving in Islamic banking and gender plays a role as a moderating variable between learning Islamic banking and Islamic financial inclusion on interest in saving in Islamic banking significantly. But gender cannot moderate between Islamic financial literacy as well as religiosity on the interest in saving at Islamic Bank for State University students in Surabaya.